The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1007/bf01986386
|View full text |Cite
|
Sign up to set email alerts
|

Open heart surgery increases the levels of histamine in arterial and coronary sinus blood

Abstract: The possible release of histamine into the coronary circulation during reperfusion of the cold, cardioplegic heart was investigated during open heart surgery in 13 patients (cardioplegic arrest 54 (35-120 min) (median (range)), cardiopulmonary bypass (CPB) 96 (65-360) min. Samples were drawn concomitantly from coronary sinus and arterial blood before cardioplegia and during myocardial reperfusion for measurement of histamine (radioenzymatic method). Additional arterial samples were drawn pre-, per- and postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…The systemic histamine levels may have been increased before start of the procedure due to anaesthesia, as morphine, thiopental, and vancuronium induce release of histamine [23]. Before ventricular fibrillation the arterial histamine level was higher than that in the coronary sinus, confirming previous observations that histamine is taken up in the human coronary circulation [8], as in all other mammals investigated [7]. We do not have a good explanation for why arterial histamine decreased 5 rain after fibrillation.…”
Section: Inflamm Ressupporting
confidence: 82%
See 3 more Smart Citations
“…The systemic histamine levels may have been increased before start of the procedure due to anaesthesia, as morphine, thiopental, and vancuronium induce release of histamine [23]. Before ventricular fibrillation the arterial histamine level was higher than that in the coronary sinus, confirming previous observations that histamine is taken up in the human coronary circulation [8], as in all other mammals investigated [7]. We do not have a good explanation for why arterial histamine decreased 5 rain after fibrillation.…”
Section: Inflamm Ressupporting
confidence: 82%
“…In previous experimental studies on cardiac histamine levels models of ischaemia-reperfusion have been employed, and the ischaemic episodes have lasted for a minimum of 10 minutes [5, 8-11, 19, 20]. Increased coronary sinus levels of histamine were found after ischaemia-reperfusion injury in dogs [9,19], guinea pigs [10,20], rats [5,11], and humans [8]. Histamine in the coronary circulation increased rapidly upon reperfusion of the ischaemic heart [5,8,9,11].…”
Section: Inflamm Resmentioning
confidence: 96%
See 2 more Smart Citations
“…Some studies have reported that during myocardial ischemia and reperfusion, histamine is released from the heart of rats (9), dogs (10,11), guinea pigs (12,13), and humans (14,15). Histamine is known to be one of the chemical mediators with inotropic and chronotropic actions and is also a vasoactive and arrhythmogenic substance (16 -18).…”
Section: Introductionmentioning
confidence: 99%